Conscience and conviction the case for civil disobedience - Brownlee, Kimberley, 1978- (Oxford : Oxford University Press, 2013)
When is it justified to disobey the law? How should the law respond to instances of conscientious disobedience? This book presents the first full-length philosophical examination of the morality and legality of civil disobedience, and the legitimate responses to civil dissent open to the state.
Description based on online resource; title from PDF title page (viewed on Oct. 31, 2012).
Includes bibliographical references and index.
Keywords: Civil disobedience; Civil disobedience -- Moral and ethical aspects